Photoacoustic phasoscopy super-contrast imaging correlating optical absorption and scattering - Gao, Fei (2014)
Phasoscopy is a recently proposed concept correlating electromagnetic (EM) absorption and scattering properties based on energy conservation. Phase information can be extracted from EM absorption induced acoustic wave and scattered EM wave for biological tissue characterization. In this paper, a novel imaging modality, termed photoacoustic phasoscopy (PAPS) imaging, is proposed and verified experimentally based on phasoscopy concept with laser illumination. Both endogeneous photoacoustic wave and scattered photons are collected simultaneously to extract the phase information, and phasoscopy image is then reconstructed by mapping phase distribution. The phasoscopy imaging experiments on vessel-mimicking phantom and ex vivo porcine tissues demonstrate significantly improved contrast than conventional photoacoustic imaging.